PENGARUH PENDAPATAN ASLI DAERAH, DANA ALOKASI UMUM, DANA ALOKASI KHUSUS, DAN DANA BAGI HASIL TERHADAP BELANJA MODAL PADA KABUPATEN/KOTA DI JAWA TENGAH PERIODE TAHUN 2013-2016 - Yoga Nogiasta, 14.05.52.0137; Wahyudi, Djoko (Students' Journal of Accounting and Banking, 2018)
The purpose of this study was toanalyze whether the Local Revenue, General Allocation Funds, Special Allocation Funds, and Revenue Sharing Funds effect Capital Expenditures districts/cities in Central Java. The sample used in this study is 35 districts/cities in Central Java, which are sourced from the report on the realization of Actual Income and Expenditure Budgets from the years 2012-2015. The analitical tool used is multiple linier regression with t test, f test, and test the coefficient of determination. The result of this research shows that Local Revenue, General Allocation Funds, Special Allocation Funds, and Revenue Sharing Funds have a significant positive effect on Capital Expenditure. Keywords: Local Revenue, General Allocation Funds, Special Allocation Funds, and Revenue Sharing Funds, Capital Expenditures